2022
DOI: 10.3390/su14031142
|View full text |Cite
|
Sign up to set email alerts
|

Child-Pedestrian Traffic Safety at Crosswalks—Literature Review

Abstract: Child pedestrians make up 30% of the total number of children injured in road traffic in the EU. They are a particularly vulnerable subgroup because they exhibit specific traffic behavior related to cognitive and physical development, sociodemographic characteristics, and environmental conditions. This paper provides an overview of research of parameters that affect the safety of children in the conflict zones of the intersection—crosswalks. The overview was undertaken targeting available research mostly condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…A young child may dart out or run into the street to retrieve a toy or a ball or to cross the street with a lack of attention to the oncoming traffic. An older child may be cognitively capable of making traffic safety decisions, though they may misjudge speed, distance, and acceleration, and may engage in risky behaviors, such as walking while distracted or using their smartphones (Deluka-Tibljaš et al 2022). We also found that the fatality risk was increased for child cyclists aged 0-19 due to cyclist midblock-failure to yield.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A young child may dart out or run into the street to retrieve a toy or a ball or to cross the street with a lack of attention to the oncoming traffic. An older child may be cognitively capable of making traffic safety decisions, though they may misjudge speed, distance, and acceleration, and may engage in risky behaviors, such as walking while distracted or using their smartphones (Deluka-Tibljaš et al 2022). We also found that the fatality risk was increased for child cyclists aged 0-19 due to cyclist midblock-failure to yield.…”
Section: Discussionmentioning
confidence: 67%
“…Education and enforcement may also target driver behaviors, such as slowing down and yielding to pedestrians/cyclists, following speed limits, never driving under the influence of alcohol and/or drugs, and other recommended behaviors to ensure safety (National Center for Statistics and Analysis 2020a, b; Stevenson et al 2015). Parental and adult supervision encourages children to walk slowly and engage in less risky behavior (Deluka-Tibljaš et al 2022). Further, engineering can support changes to the built environment, including measures such as building sidewalks and well-lit streets, reducing traffic speed and volume, and adding speed bumps and roundabouts to reduce injury (Cloutier et al 2021), as well as features of the motor vehicle (e.g., backup cameras, blind-spot detection, lane departure technology, and advanced sensor technology that can prevent collision).…”
Section: Discussionmentioning
confidence: 99%
“…Head-swinging increased toward the entry point of the crosswalk and at the crossing point. Deluka-Tibljaš et al took up a study summary carried out in the world about the road safety of walking children at pedestrian crossings in the past 10 years [10]. For a further study, we suggested that the influence on road safety of the children was analyzed by distractions in detail.…”
Section: Introductionmentioning
confidence: 99%